KINERJA DINAS SOSIAL DALAM PEMBERIAN REHABILITASI SOSIAL KEPADA PENYANDANG DISABILITAS DI KOTA DENPASAR - Widhiana, I Made Surya; Wijaya, Komang Adi Sastra; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2024)
The provision of social rehabilitation to persons with disabilities by the Denpasar City Social Service aims to enable persons with disabilities to have independence and restore the function of persons with disabilities in society. However, in practice there are performance problems, therefore it is necessary to measure the performance of public organizations to review the performance of the Social Service in providing social rehabilitation for persons with disabilities in Denpasar City. This research uses a type of qualitative research with a descriptive approach. The data sources used are primary and secondary data. The informant determination technique in this study used purposive sampling. This study uses the theory of performance measurement of public organizations according to Agus Dwiyanto (2017). The purpose of this study was to find out how the performance of social services in providing social rehabilitation for persons with disabilities in Denpasar City. The results of the study show that the performance of the Social Service in providing social rehabilitation for persons with disabilities in Denpasar City is quite good. Indicators of service quality, responsiveness, responsibility and accountability have been running optimally while productivity indicators have not been optima